SPA AND CLIMATIC RESORTS (CENTERS) AS RESOURCES OF PROGRAM OF SPORT RECREATION IMPLEMENTATION - Ivica Nikolić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
The aspiration of the civilized man is the improvement of work which aim is to achieve as big as possible effect of productivity and as small as possible participation of labour. The result of this process, which cannot be avoided, is some kind of fatigue that has hypocinaesiological characteristics in regard to demands of modern work process. The most effective way to fight against fatigue is to have an active holiday that is meaningfully programmed, led and carried out through movement of tourists, with the addition of natural factors, among which climate and healing waters are particularly important. These very resources characterize the tourist potential of Serbia and Montenegro with lots of available facilities at 1000 m height above the sea level and spa centers with springs and a complete offer physio-prophylactic procedures and following facilities for sport recreation. The implementation of programmed active holidays in to the corpus of tourist offer of Serbia and Montenegro represents prospective of development of tourism and tourist economy with effects of multiple importance as for participants, so for the level of tourist consumption. That will definitely influence the lengthening of tourist season as the primary goal of every catering establishment. Surveys show that the affection and viewpoints of potential tourists are especially directed towards engaging sport games and activities on and in the water, as part of the elementary tourist offer in spas and climatic resorts and their available facilities. Recommendationsand postulates of program of sport recreation, which are presented through four charts, are the basis of marketing strategy of appearance on tourist market with permanent education of management personnel and further research of potential market expanding. The publication and distribution of advertising materials are especially important, both at the market in our country and at the foreign market, where the abundance and richness of tourist offer, with a special emphasis on spas and climatic resorts should be underlined.